Polymethacrylate platforms with controllable surface properties for dengue virus detection / Samira Hosseini - Hosseini, Samira (2015)
This thesis presents an effective method for synthesis and processing of polymethylmethacrylate-co-methacrylic acid (PMMA-co-MAA) biochips with controlled surface properties aimed for successful detection of the Dengue virus (DV). By variation of synthesis reaction parameters and using spin-coating technique, different compositions of the PMMA-co-MAA coated biochips were prepared. Designed coated chips have been employed for surface immobilization of the Dengue antibody molecules and further detection of DV through antibody/antigen coupling. Biomolecule immobilization on the functionalized surfaces of the chips was performed via different techniques including: 1) physical adsorption of the antibody on the surface; 2) covalent immobilization of the antibody on the surface through carbodiimide chemistry; and 3) antibody immobilization via different sizes of the amine-bearing surface spacers, hexamethylenediamine (HMDA) and polyethyleneimine (PEI). Results have shown a higher detection signals generated from polymer coated biochips in comparison to the conventional enzyme-linked immunosorbent assay (ELISA). Particularly, the presence of amine spacers on the surface enhanced the detection signal up to the considerable levels ( 8 times higher signal intensity than conventional method). Developed biochips in this study are privileged with strong and permanent presence of surface carboxyl (–COOH) groups that can be essential in successful protein immobilization and subsequent detection of the DV. Presented biochips have shown a great potential for future integration into the biodiagnostic tools such as microfluidic devices. Such protein-friendly platforms can be employed for detection of different types of viruses not just limited to DV.